Serrivomer beanii Gill & Ryder 1883 - Fermon, Yves; Bailly, Nicolas; Cardiec, Floriane; Causse, Romain; Chartrain, Emmanuel; Chirio, Laurent; Bruyne, Godefroy De; Deynat, Pascal; Hopkins, Carl D.; Lamboj, Anton; Mennesson, Marion I.; Beh, Jean-Hervé Mve; et al. (Zenodo, 2022)
Serrivomer beanii Gill & Ryder, 1883 Occurrence: native Maximum length: 78 cm TL Water type: marine Environment: bathypelagic Depth range: 0-5998 m Migration: unknown IUCN status: LC – Least concern (2015) Source: bibliography, preserved Distribution and remarks: Atlantic Ocean: known on both sides, between 60°N and 20°S. In the eastern Atlantic, reported to range further north to Iceland and further south to off the Cape and Natal in South Africa. Published as part of Fermon, Yves, Bailly, Nicolas, Cardiec, Floriane, Causse, Romain, Chartrain, Emmanuel, Chirio, Laurent, Bruyne, Godefroy De, Deynat, Pascal, Hopkins, Carl D., Lamboj, Anton, Mennesson, Marion I., Beh, Jean-Hervé Mve, Paugy, Didier, Sidlauskas, Brian, Sullivan, John P., Weghe, Jean-Pierre Van De, Vigliotta, Thomas R. & Zee, Jouke Van Der, 2022, An annotated checklist of the fishes of Gabon, pp. 2-3 in Cybium 46 (2) on page 121, DOI:10.26028/cybium/2022-462-3-001, http://zenodo.org/record/13153873